Mental disorders are no predictors to determine the duration of cannabis-based treatment for chronic pain - Rometsch, Caroline; Ott, Stephan; Festl-Wietek, Teresa; Jurjut, Anna-Maria; Schlisio, Barbara; Zipfel, Stephan; Stengel, Andreas; Herrmann-Werner, Anne (Frontiers in Psychiatry, 2023)
Background: A complex biopsychosocial disorder with a global prevalence of up to 33%, chronic pain (CP) can be treated by following multidisciplinary approaches that may include cannabis-based medicine (CBM). However, because CBM continues to be a new treatment, questions remain regarding the ideal duration for CBM and its psychosocial determinants, including mental comorbidities. Method: In a retrospective cross-sectional study involving 46 patients with CP (ICD-10 code F45.4-), three validated instruments—the German Pain Questionnaire, the Depression Anxiety Stress Scale, and the Marburg Questionnaire of Habitual Well-Being—were used to identify pain-specific psychosocial determinants and mental disorders. Descriptive analyses, a group differences analysis, and a logistic regression analysis were performed using SPSS. Results: The patients most frequently reported low back pain as the primary location of their CP, and in attributing the condition to tissue damage, most had largely adopted a somatic orientation in conceptualizing their illness. Most had experienced CP for more than 5 years (M = 5.13 years, SD = 1.41) and, as a consequence, faced significant restrictions in their everyday life and exhibited low subjective well-being (MFHW median = 4.00, N = 43, Q1: 2.00, Q3: 9.00, range: 0–20). Comorbidities among the patients included depression, (DASS-Depression, median: 11.50, Q1: 7.00, Q3: 16.25), anxiety (DASS-Anxiety, median: 4.50, Q1: 2.75, Q3: 8.00), and stress (DASS-Stress, median: 11.00, Q1: 7.00, Q3: 15.00). Between two cannabis-based treatments with a course lasting either less or more than a year, duration of treatment showed no between-group differences in terms of sociodemographic factors, pain-specific factors, conceptualizations of the illness, or mental disorders. Psychosocial determinants such as subjective well-being and mental comorbidities were not significant predictors of the duration of cannabis-based treatment. Conclusion: We found no evidence indicating that the benefits of short-term versus long-term cannabis-based treatment can be predicted by mental comorbidities or psychosocial factors. However, because CBM may be included in approaches to treat CP, questions about the ideal duration of such treatment remain to be answered.